Incidence of common illness and non-work-related accidents, and economic costs generated by temporary disability. Canary Islands (2018-2021) (Medicina y Seguridad del Trabajo, 2025)
Introduction: Temporary incapacity due to common illness and non-work-related accidents is a contingency that has its causes in personal, environmental, economic, and social factors. Our goal is to understand the incidence based on the worker’s occupation and its costs.”Methods: Observational epidemiological study of a retrospective and cross-sectional nature involving an average annual population of 805,450 affiliates registered with the National Social Security Institute during the four-year period from 2018 to 2021 in the Autonomous Community of the Canary Islands, with an average of 237,586 annual cases of common temporary disability (IT). Measures of central tendency and dispersion were calculated for quantitative variables, as well as frequencies and percentages for qualitative variables, omitting statistical significance tests since the entire population was included. The cost of temporary disability was calculated by imputing average salaries based on the year of study, the worker’s sex, and the occupation sector according to the CNO-11, according to the human capital theory which states that salary is equivalent to a worker’s productivity.Results: The incidence rate has been evolving upwards since 2018, starting at 24.8%, rising to 29.5% in 2019, and reaching 37.2% in 2021. It only experiences a slight decrease in 2020, dropping to 28.2%. The costs in the Canary Islands ranged from 568 million euros in 2018, 663 million in 2019, 412 million in 2020, and 589 million in 2021. The total sum of this expenditure exceeds 2.2 billion euros. Women incurred slightly higher costs than men, and the age group most affected in economic terms was those aged 46 to 55 years. According to the CNO-11 classification, the group with the highest expenditure is represented by workers in the restaurant, personal services, protection, and sales sectors (1-CNO-11), followed by technicians and scientific and intellectual professionals (2-CNO-11), and in third place, elementary occupations (9-CNO-11).Conclusions: The incidence rate of temporary disability has experienced a progressive increase between 2018 and 2021, suggesting a deterioration of the Occupational Health situation in the Canary Islands, influenced by the COVID-19 pandemic with a rise in cases related to the virus, and a decrease in other diagnoses due to lockdown measures. Low back pain, caused by stress, anxiety, improper postures, repetitive movements, or excessive strain, is the most common condition in the Canary Islands as a cause of temporary disability. We also know that the occupational group in the restaurant, personal services, protection, and sales sectors is the most affected by temporary disability processes. Therefore, if working hours were reduced or breaks were normalized, productivity could increase. Understanding the impact that these cases have had on various occupations of workers according to the CNO-11, companies will be able to evaluate proposals to implement programs for the promotion and prevention of workplace illnesses, as well as suggest improvements in the organization of health services in order to reduce absenteeism due to illness.
Keywords: Occupational health, sick leave, incidence, occupations, cost allocations